IMPLEMENTATION OF MURABAHAH CONTRACT IN FINANCING HOME OWNERSHIP TAKE OVER (PPR) AT BANK SYARIAH INDONESIA (BSI) KCP SIDOARJO KRIAN IN A REVIEW OF DSN MUI FATWA - Muftaqor, Nur Azmil; Setiyowati, Arin; Huda, Fatkhur; Nasution, Hafizul Ilmi (Ekonomi Islam, 2025)
Research aims: This study analyzes the implementation of the Murabahah contract in take-over Financing for home Ownership Financing at Bank Syariah Indonesia (BSI) KCP Sidoarjo Krian, with emphasis on Sharia compliance, transaction transparency, and procedural integrity. Design/Methodology/Approach: A qualitative‐descriptive design was adopted. Primary data were gathered through in‐depth interviews with key bank officials and supplemented by document analysis. Data were processed via reduction, presentation, and thematic interpretation. Research findings: Results indicate that the BI‐Checking stage is pivotal for assessing customer creditworthiness and mitigating financing risk. BSI KCP Sidoarjo Krian demonstrates Sharia adherence by disclosing detailed cost breakdowns and profit margins before contract execution, reflecting principles of honesty and fairness. Theoretical Contribution/Originality: This study proposes a structured set of guidelines to enhance Murabahah-based takeover mechanisms. Notable recommendations include standardized disclosure practices, regular reassessment of repayment capacity, and strengthened notarial collaboration to ensure legal compliance. Practitioners/Policy Implications: The study underscores the need for a nationally standardized framework across Islamic financial institutions to optimize operational efficiency, foster inclusive financial access, and reinforce public trust in Sharia-compliant financing systems. Research Limitations/Implications: Given its institution-specific focus on BSI KCP Sidoarjo Krian, generalization across other Islamic banks may be limited. Further research is recommended to evaluate the model’s applicability in diverse institutional and regional contexts.